FIGURES OF SPEECH OF NGEKHANE IN ALAS WEDDING CEREMONY - Halim, Abdul (TABULARASA, 2013)
This article addresses figures of speech of Ngekhane in Alas wedding ceremony. The data were taken from Ngekhane text recorded in Alas wedding ceremony . The method of the research is descriptive. It gives description about the figures of speech used in Alas wedding ceremony. The findings show that there are seventeen figures of speech but figures of speech used in Alas wedding ceremony only six figures of speech namely simile, merism, repetition, hyperbole, metaphor, meiosis / litotes. From the six figures of speech used in Alas wedding ceremony, merism was dominantly used in Alas wedding ceremony it was indicated that Alas people was very clear and brief in speaking. Suitable with the function of merism was as an addition explanation of the sentence and to clarify the meaning of the sentence. Those figures of speech were reflected Alas culture value namely politeness, friendliness, respect the older, and resoluteness .